UNIVERSALITAS DAN LOKALITAS HUKUM ISLAM - A. Malthuf Siroj (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
Islamic law has two dimensions at once, namely universality and locality. In contemporary Islamic legal thought, there are two trends that contain mutual attraction between the two to bring dimension of locality to the dimension of universality on one side, and vice versa on the other side. As a consequence, there will be two possibilities, absoluteness or relativization of Islamic law. The legal discourse increasingly gains its own intensity in recently in line with the development of science and the use of various approaches in the study of Islamic law. Islamic law that is universally used is called syari`ah. This syariah law is rules of Allah SWT that is produced from texts with qath’î quality either from the side of the existency or the meanings without human beings rasional (ra’y) intervention because those texts are not the object of Ijtihad. Meanwhile, local Islamic Law is called fiqh. It is the law which is produced from texts with zhannî quality and becomes an object of Ijtihad. Because Fiqh is the result of Ijtihad so that it is usual when there are many madzhabs on it. Therefore, this paper will put this issue in proportion to find common ground between the two trends of contemporary Islamic legal thought. So that, it will hopefully clear up us the limits of universality and locality dimension of Islamic law, a focus of this legal discourse.